Decoupling of Global Brain Activity and Cerebrospinal Fluid Flow in Parkinson's Disease Cognitive Decline - Han, Feng; Brown, Gregory L.; Zhu, Yalin; Belkin‐Rosen, Aaron E.; Lewis, Mechelle M.; Du, Guangwei; Gu, Yameng; Eslinger, Paul J.; Mailman, Richard B.; Huang, Xuemei; Liu, Xiao (Movement disorders, 2021)
ABSTRACT Background Deposition and spreading of misfolded proteins (α‐synuclein and tau) have been linked to Parkinson's disease cognitive dysfunction. The glymphatic system may play an important role in the clearance of these toxic proteins via cerebrospinal fluid (CSF) flow through perivascular and interstitial spaces. Recent studies discovered that sleep‐dependent global brain activity is coupled to CSF flow, which may reflect glymphatic function. Objective The objective of this current study was to determine if the decoupling of brain activity–CSF flow is linked to Parkinson's disease cognitive dysfunction. Methods Functional and structural MRI data, clinical motor (Unified Parkinson's Disease Rating Scale), and cognitive (Montreal Cognitive Assessment [MoCA]) scores were collected from 60 Parkinson's disease and 58 control subjects. Parkinson's disease patients were subgrouped into those with mild cognitive impairment (MoCA < 26), n = 31, and those without mild cognitive impairment (MoCA ≥ 26), n = 29. The coupling strength between the resting‐state global blood‐oxygen‐level‐dependent signal and associated CSF flow was quantified, compared among groups, and associated with clinical and structural measurements. Results Global blood‐oxygen‐level‐dependent signal–CSF coupling decreased significantly (P < 0.006) in Parkinson's disease patients showing mild cognitive impairment, compared with those without mild cognitive impairment and controls. Reduced global blood‐oxygen‐level‐dependent signal–CSF coupling was associated with decreased MoCA scores present in Parkinson's disease patients (P = 0.005) but not in controls (P = 0.65). Weaker global blood‐oxygen‐level‐dependent signal–CSF coupling in Parkinson's disease patients also was associated with a thinner right entorhinal cortex (Spearman's correlation, −0.36; P = 0.012), an early structural change often seen in Alzheimer's disease. Conclusions The decoupling between global brain activity and associated CSF flow is related to Parkinson's disease cognitive impairment. © 2021 International Parkinson and Movement Disorder Society